Association Between Shock Index and Post-Emergency Intubation Hypotension in Patients Who Called the Rapid Response Team at Dr. Cipto Mangunkusumo Hospital - Rahmah, Herlina; Adisasmita, Asri; Manggala, Sidharta Kusuma; Sugiarto, Adhrie; Zahrina, Fadiah; Rosdiana, Prita (Indonesian Journal of Anesthesiology and Reanimation, 2023)
Introduction: Hypotension is an acute complication following Emergency Endotracheal Intubation (ETI) in populations who called the Rapid Response Team (RRT). Thus, a fast and simple tool is needed to identify the risk of Post-emergency Intubation Hypotension (PIH). Shock Index (SI) pre-intubation is one of the potential factors to predict PIH. Objective: To measure the association between shock index with post-emergency intubation hypotension after calling for the RRT. Methods: This research is a cohort retrospective study that analyzed 171 patients aged â‰¥18 years who have called RRT and underwent an emergency ETI. The cut-off point for SI was determined using the ROC curve to predict PIH. The modification effect was evaluated using stratification analysis. Data were analyzed using cox regression to determine the likelihood of SI in the cause of hypotension. Result: A total of 92 patients (53.8%) underwent post-emergency intubation hypotension. The SI cut-off point of 0.9 had a sensitivity of 82.6% and a specificity of 67.1% for predicting PIH (Area Under Curve (AUC) 0.81; 95% CI 0.754–0.882, p <0.05). The increased risk of PIH associated with high SI score was an aRR of 1.9; 95% CI 1.03–3.57, a p-value of 0.040 among those with sepsis, and an aRR of 7.9, 95% CI 2.36–26.38, a p-value of 0.001 among those without sepsis. Conclusion: This study showed that a high SI score was associated with PIH after being controlled with other PIH risk variables. The risk of PIH associated with SI score modestly increased (2-fold increase) in those with sepsis and significantly increased (8-fold increase) in those without sepsis.